Analysis of Educational Values in the Journal for Children and Youth Entitled Milodarke - Lenard, Ivan; BOŽIĆ LENARD, Dragana (Anafora, 2023)
Through a content analysis of the first journal for children and youth in Osijek, Milodarke, this paper identifies, categorizes, and elaborates on the educational values addressed in the journal. The journal for children and youth, Milodarke – An Illustrative Journal for Croatian Youth, was published from the fall of 1913 until the spring of 1914. The journal was published in five issues, and was launched with the aim to provide children and youth living in the city of Osijek and the region of Slavonia with educational and pedagogical reading materials. The paper employs methods of historical content and quantitative analysis. The quantitative analysis was used to determine the number of elements of children’s literature in the journal as well as the number of specific educational values. The identification and elaboration of the recognized educational values were done using the content analysis method. The analysis has pointed to poems as the most represented literary element, followed by tales and parables. The content analysis has shown that the most fostered educational values were in the category of personal characteristics, such as fairness, respect, sacrifice, wisdom, pride, loyalty, resourcefulness, and honesty. In addition, educational values in the categories of universal, family, and religious values were also strongly encouraged. The research points to the usage of educational values for acquiring knowledge and developing children’s and youths’ self-identities in Osijek and Slavonia.